The creative age : awakening human potential in the second half of life - Cohen, Gene D. (New York, NY : Quill, 2001)
The author shows how the unique combination of age, experience, and creativity can produce inner growth and potential for everyone.
Includes bibliographical references (p. [359]-366) and index.
Keywords: Middle age -- Psychological aspects; Creative ability in old age